Perceptions Regarding Daith Piercing in Migraine, A Survey of Pediatric Patients - Trevor Gerson; Mark Connelly; Madeline Boorigie; Jennifer Bickel; Jennifer Dilts (J, 2020)
The treatment of migraine is evolving to include non-traditional approaches, as pharmacologic therapy alone is unsuccessful in many patients. Daith piercing, a cartilaginous ear piercing, has become popular as a potential nonpharmacological treatment option for migraine. However, there are no systematic data on the utilization and efficacy of these piercings. Therefore, we investigated the perceptions of pediatric patients regarding Daith piercing and gathered initial retrospective data for patients who had already received it. Patients presenting to a pediatric neurology clinic were invited to complete a questionnaire to assess knowledge about and attitudes towards Daith piercing and their willingness to undergo such a treatment. For those with a Daith piercing, the effects on headaches, function, and mood were evaluated. Of the 171 respondents, 61% had prior knowledge of Daith piercings, 27% knew someone with a Daith piercing, and 60% of patients presenting with headache were willing to undergo piercing. Of the eight patients (5% of respondents) who had already undergone piercing, six (75%) reported improvement in headaches, five (62%) had missed fewer days of school or work, and seven (87%) reported mood improvement. The high proportion of pediatric patients willing to undergo this form of treatment speaks to the desire for and acceptance of nonpharmacologic treatments. Although based on a small sample, the data from children who have already undergone Daith piercing is promising and supports a need for further systematic investigation into this treatment approach.